Financial Statement Analysis to Assess the Financial Performance of ohe Dki Jakarta Provincial Government Fiscal Years 2021–2024 - Fauzia, Melia; Rizki, Mhd. Nanda; Surahman, Nabilah Putri; Arihan, Reva Putri; Khairunnisa; Laia, Tri Putrianis; Nasution, Anggi Pratama (CV Raskha Media Group, 2025)
The purpose of this study is to measure the performance of the DKI Jakarta provincial government's financial reports and to improve the quality of regional financial management performance. The research method used is descriptive quantitative. The data collection technique used is documentation using data from 2021 to 2024. The results of the study show that the regional financial independence ratio is high, with an average of 226%, the regional financial dependency ratio is low at 30%, the fiscal decentralization ratio is very high at 67.48%, the PAD effectiveness ratio is quite effective at 94%, the PAD efficiency ratio is inefficient at 95.08%, the effectiveness of regional taxes is very effective at 102%, the efficiency ratio of regional taxes is inefficient at 42.83%, and the contribution ratio of BUMD is very good at 106%. Based on the results of the DKI Jakarta ratio measurement, its financial report performance is good, as can be seen from the high Regional Financial Independence Ratio, Low Regional Financial Dependence Ratio, and Very High Fiscal Decentralization Ratio. sufficiently effective PAD effectiveness, excellent BUMD contribution level, and very effective local tax effectiveness. However, improvements are needed in the efficiency ratio and local tax efficiency ratio.